2011
DOI: 10.1016/j.tibs.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The Ras-ERK and PI3K-mTOR pathways: cross-talk and compensation

Abstract: The Ras-ERK (extracellular signal-regulated kinase) and PI3K (phosphatidylinositol 3-kinase)-mTOR (mammalian target of rapamycin) signaling pathways are the cell’s chief mechanisms for controlling cell survival, differentiation, proliferation, metabolism, and motility in response to extracellular cues. Components of these pathways were among the first to be discovered when scientists began cloning proto-oncogenes and purifying cellular kinase activities in the 1980s. Ras-ERK and PI3K-mTOR were originally model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
1,360
6
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,532 publications
(1,426 citation statements)
references
References 99 publications
45
1,360
6
15
Order By: Relevance
“…The ERK1/2 signaling pathway has the ability to regulate proteins involved in the initiation and elongation stages of mRNA translation in an mTOR-dependent and -independent manner (28,35,43,44). Recent studies indicated that ERK signaling is involved in later phase anabolic responses after resistance exercise (5,6,15).…”
Section: Discussionmentioning
confidence: 99%
“…The ERK1/2 signaling pathway has the ability to regulate proteins involved in the initiation and elongation stages of mRNA translation in an mTOR-dependent and -independent manner (28,35,43,44). Recent studies indicated that ERK signaling is involved in later phase anabolic responses after resistance exercise (5,6,15).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In addition, Ras proteins can also activate PI3K, mediating proliferative and survival signals. 10,11 The GAP domain of DAB2IP is homologous to other RasGAPs, such as GAP120 and neurofibromin (NF1), and can stimulate the GTPase activity of RAS proteins both in vitro and in cancer cell lines (Figure 2). [12][13][14][15] In prostate cancer cells, DAB2IP was shown to be recruited by the adaptor protein DAB2/DOC2 to promote Ras inactivation and inhibition of MAPK signaling upon receptor stimulation.…”
Section: Dab2ip: a Complex Gene Encoding A Negative Modulator Of Multmentioning
confidence: 99%
“…The GAP activity of DAB2IP can further enforce inhibition of the PI3K-AKT axis by reducing Ras-dependent activation of PI3K p110α subunit. 10,11 Interestingly, animal models showed that DAB2IP functions as endogenous inhibitor of adaptive angiogenesis in part by binding directly to VEGFR-2 and limiting PI3K activation ( Figure 4b). 4 GSK3β-β-catenin signaling.…”
Section: Dab2ip: a Complex Gene Encoding A Negative Modulator Of Multmentioning
confidence: 99%
“…Important signal-transduction pathways linking regulation of protein synthesis to nutrient sensing are mitogen-activated protein kinase and target of rapamycin signalling cascades. However, as the connection of these signalling pathways to translational regulation and cell growth has been extensively reviewed, they will not be further discussed here (for more information see reviews [11][12][13][14]). …”
Section: Introductionmentioning
confidence: 99%